Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2002
DOI: 10.2527/2002.8061528x
|View full text |Cite
|
Sign up to set email alerts
|

Effect of nutrient intake on the development of the somatotropic axis and its responsiveness to GH in Holstein bull calves1

Abstract: We investigated the effect of increasing nutrient intake on the responsiveness of the GH/IGF-I system in calves fed a high-protein milk replacer. Fifty-four Holstein bull calves were fed one of three levels (low, medium, and high; n = 18 per treatment) of a 30% crude protein, 20% fat milk replacer to achieve target rates of gain of 0.50, 0.95, or 1.40 kg/d, respectively, for low, medium, and high. Six calves per treatment were slaughtered at approximately 65, 85, and 105 kg BW. Additionally, six calves were sl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

18
70
1
3

Year Published

2003
2003
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 87 publications
(93 citation statements)
references
References 0 publications
18
70
1
3
Order By: Relevance
“…Consistent with this conclusion, we demonstrated in the current experiment that elevated plane of nutrition had few effects on transcript abundance in the mammary gland. This was the case even for IGF-I, a gene we previously demonstrated to respond dynamically to nutrition in the liver of growing cattle (Smith et al 2002). This lack of effect is consistent with the data of Weber et al (2000) who observed similar IGF-I mRNA abundance in the parenchyma of prepubertal heifers growing 0 .…”
Section: Discussionsupporting
confidence: 80%
“…Consistent with this conclusion, we demonstrated in the current experiment that elevated plane of nutrition had few effects on transcript abundance in the mammary gland. This was the case even for IGF-I, a gene we previously demonstrated to respond dynamically to nutrition in the liver of growing cattle (Smith et al 2002). This lack of effect is consistent with the data of Weber et al (2000) who observed similar IGF-I mRNA abundance in the parenchyma of prepubertal heifers growing 0 .…”
Section: Discussionsupporting
confidence: 80%
“…There was a positive influence of IGF1 on both weight and ADG, confirming results of an earlier study (Brickell et al, 2009b). IGF1 production is in part controlled by nutrient intake and IGF1 is a known regulator of muscle development (Bass et al, 1999;Smith et al, 2002). IgG at recruitment also had a small positive effect on growth, implying that calves benefited from a high initial intake of CI for parameter estimate: * P < 0.05, ** P < 0.01, *** P < 0.001.…”
supporting
confidence: 75%
“…Growth hormone treatment up-regulates hepatic growth hormone binding sites in sheep, but not in lambs (Sauerwein et al 1991, Min et al 1999. Although growth hormone stimulated hepatic IGF-I mRNA levels up to day 14 in our study, plasma concentrations of IGF-I in the GH group did not increase before day 42 in our study, as is known for cattle (Elsasser et al 1989, Holzer et al 2000, Smith et al 2002. Because hepatic IGF-I is the main source for circulating IGF-I in cattle (Pfaffl et al 1998, Cordano et al 2000, it may take some time before the mature IGF-I peptide is delivered to the circulation.…”
Section: Discussionmentioning
confidence: 44%